b - Gamble, R. (b)
The first comprehensive overview of the life and writings of the Third Karmapa Rangjung Dorje, a revolutionary figure in the Kagyu tradition of Tibetan Buddhism. Known for his mastery of teachings across sectarian lines, his treatises on medicine and astrology, and his work as spiritual advisor to the last Yuan emperor of China, Rangjung Dorje (1284-1339) is considered one of the most important and influential figures in Tibetan Buddhist history. First recognized as a tulku, or reincarnated Buddhist master, at the age of five, Rangjung Dorje became the Karma Kagyu lineage holder and instituted the reincarnation-based inheritance structure within Tibetan Buddhism that led to the formation of important lineages of tulkus such as the Dalai Lamas. In this groundbreaking work, Ruth Gamble synthesizes her extensive research on Rangjung Dorje into a sweeping biography covering his life, legacy, and important selected writings. Included in her discussions are Rangjung Dorje's synthesis of Dzogchen and Mahamudra in his writings, his devotion to spreading the teachings of Buddha nature, and several works never before translated into English. As the most comprehensive work available on Rangjung Dorje, this book is an indispensable resource for scholars and Buddhist practitioners alike.
Includes references and index.